The Relationship Between Body Mass Index and Hypertension Incidents among the Elderly - Dini Tiarani Puspita Sari; Musthika Wida Mashitah (Health and Technology Journal (HTechJ), 2026)
Hypertension is a prevalent health concern among older adults and is strongly associated with increased Body Mass Index (BMI). Excess body weight contributes to elevated blood pressure through physiological mechanisms, including increased peripheral vascular resistance and heightened sympathetic nervous system activity. This study aimed to examine the association between BMI and hypertension prevalence among older adults. An analytical observational study with a cross-sectional design was conducted among 60 older adults selected through purposive sampling. Data were collected using standardized procedures, including measurements of body weight, height, and blood pressure. BMI was categorized according to standard criteria. The association between BMI and hypertension was analyzed using Fisher's Exact Test, with α = 0.05. The prevalence of hypertension among participants was 58.3%. Higher proportions of hypertension were observed in overweight (68.2%) and obese (80.0%) individuals compared to those with normal BMI. Statistical analysis revealed a significant association between BMI and hypertension (p = 0.012). BMI is significantly associated with hypertension among older adults. These findings highlight the importance of weight management through nutritional education, physical activity promotion, and routine blood pressure monitoring as part of comprehensive elderly healthcare services.